The screenwriter's problem solver how to recognize, identify, and define screenwriting problems - Field, Syd
All writing is rewriting. But what do you change, and how do you change it? All screenplays have problems. They happened to Die Hard: With a Vengeance and Broken Arrow--and didn't get fixed. leave the films flawed. They nearly shelved Platoon--until Oliver Stone rewrote the first ten pages and created a classic. They happened to every screenwriter. But good writers see their problems as a springboard to creativity. Now bestselling author Syd Field, who works on over 1,000 screenplays a year, tells you step-by-step how to identify and fix common screenwriting problems, providing the professional secrets that make movies brilliant--secrets that can make your screenplay one headed for success...or even Cannes.